2004
DOI: 10.1175/1520-0469(2004)061<0961:lvitma>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Variability in the Midlatitude Atmosphere Induced by an Oceanic Thermal Front

Abstract: This study examines the flow induced in a simple atmospheric model by an east-west oriented oceanic thermal front. The model has a linear marine boundary layer coupled to a quasi-geostrophic, equivalent-barotropic free atmosphere. An eastward jet, parallel to the oceanic front's isotherms, characterizes the flow induced in the free atmosphere by the vertical velocity at the top of the boundary layer. A large gyre develops on either side of this jet, cyclonic to the north and anticyclonic to the south of it. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
98
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 52 publications
5
98
1
Order By: Relevance
“…The sign, magnitude, and spatial pattern of this feedback inferred from GCM results is, however, controversial; compare, for example, Peng et al (1995Peng et al ( , 1997 and Kushnir and Held (1996). In general, the linear response of the atmospheric circulation to SST anomalies associated with mid-latitude variability is weak; see, however, Feliks et al (2004Feliks et al ( , 2007. Kravtsov et al (2006bKravtsov et al ( , 2007a, in their idealized quasi-geostrophic (QG) oceanatmosphere model, have recently identified a novel type of coupled behavior in which atmospheric nonlinearity plays a key role.…”
Section: Introductionmentioning
confidence: 99%
“…The sign, magnitude, and spatial pattern of this feedback inferred from GCM results is, however, controversial; compare, for example, Peng et al (1995Peng et al ( , 1997 and Kushnir and Held (1996). In general, the linear response of the atmospheric circulation to SST anomalies associated with mid-latitude variability is weak; see, however, Feliks et al (2004Feliks et al ( , 2007. Kravtsov et al (2006bKravtsov et al ( , 2007a, in their idealized quasi-geostrophic (QG) oceanatmosphere model, have recently identified a novel type of coupled behavior in which atmospheric nonlinearity plays a key role.…”
Section: Introductionmentioning
confidence: 99%
“…The linear response is expected to be weak, but nonlinear modes of atmospheric variability, such as SAM, may produce a stronger effect (Koo et al, 2002;Kravtsov et al, 2006a, b). Feliks et al (2004Feliks et al ( , 2007 have shown, in particular, how an oceanic thermal front may induce intraseasonal variability in the overlying atmosphere, including surfacewind evolution.…”
Section: Air-sea Coupling Over the Southern Oceanmentioning
confidence: 99%
“…Several time scales now interact: these include the intrinsic variability of the double-gyre circulation, on interannual and interdecadal time scales (Simonnet, 2005;Simonnet et al, 2005), as well as atmospheric LFV, on intraseasonal and interannual time scales (Feliks et al, 2004(Feliks et al, , 2007.…”
Section: Coupled Ocean-atmosphere Models Of the North Atlantic Circulmentioning
confidence: 99%
“…The oceanic model is then coupled with the atmosphere as in Feliks et al (2004Feliks et al ( , 2007, namely it is forced by the Gulf Stream's thermal front through the advected SST and associated Ekman pumping. The atmospheric domain is a periodic channel with two different settings, i.e.…”
Section: Coupled Ocean-atmosphere Models Of the North Atlantic Circulmentioning
confidence: 99%
See 1 more Smart Citation